Protective Effect of the T1212C Macrophage Mannose Receptor Gene Polymorphism on Pulmonary Tuberculosis - Yani Triyani; Julia Hartati; Budiman Budiman; Ida Parwati; Bachti Alisjahbana (Global Medical & Health Communication (GMHC), 2022)
The interaction between the mannose receptor, which is encoded by the macrophage mannose receptor (MMR) gene, and the most virulent antigen (the mannose-capped lipoarabinomannan) cell wall of virulent strains of Mycobacterium tuberculosis trigger an innate and adaptive immune response. It also produces pro and anti-inflammatory cytokines, which play a role in the pathogenesis of tuberculosis (TB) infection. Therefore, MMR gene polymorphism is a risk factor associated with the prognosis for active pulmonary TB. This study aimed to determine the correlation between MMR gene polymorphism and active or latent pulmonary tuberculosis. In this phase, MMR gene polymorphism was analyzed using a case-control design consisting of 74 control group subjects (patients with latent TB) and 74 case groups (patients with active pulmonary TB). The subject’s MMR gene DNA sequencing examination. The study was conducted at the Teaching Hospital, Faculty of Medicine, Universitas Padjadjaran Bandung, from February 2014 to January 2015. The statistical analysis used chi-square and odds ratio. The study’s result has shown the MMR gene polymorphism factor that correlated to the incidence of active pulmonary TB was T1212C (OR=0.253; 95% CI=0.111−0.575; p=0.001). There was an MMR gene in one SNP in the control group (C1323T) only and five single nucleotide polymorphisms (SNPs) in both groups (C1303T, C1221, T1212C, G1186A, and G1195A). Therefore, it can be concluded that MMR gene polymorphism on the T1212C site correlated with the incidence of active pulmonary tuberculosis and was protective.